Pengaruh Likuiditas, Kebijakan Dividen, Profitabilitas, dan Ukuran Perusahaan pada Nilai Perusahaan - Cahyani, Gusti Ayu Putri; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p16, 2019)
Signal theory emphasizes that company information can be responded differently by investors. One method used to analyze company value is using the Price to Book Value (PBV) approach. This study aims to analyze the effect of liquidity, dividend policy, profitability, and firm size on firm value. This research was conducted on companies listed in the LQ 45 index on the Indonesia Stock Exchange in 2013-2016. The number of samples taken as many as 10 companies used the nonprobability sampling method with a purposive sampling technique, so that the number of samples during the 4 years of observation became 40 companies. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that liquidity and profitability have a positive effect on firm value, while dividend policy and company size have no effect on firm value. Keywords: Liquidity, dividend policy, profitability, company size, and company value